COVID-19 vaccination hesitancy in pregnant and breastfeeding women and strategies to increase vaccination compliance: a systematic review and meta-analysis. (3rd October 2022) - Bianchi, Francesco Paolo; Stefanizzi, Pasquale; Di Gioia, Maria Cristina; Brescia, Nazario; Lattanzio, Sabrina; Tafuri, Silvio
ABSTRACT: Introduction: Pregnant and breastfeeding women are at an increased risk of severe illness from COVID-19. Despite this, low vaccination coverages are reported in this population sub-group. Areas covered: The purpose of this study is to estimate the proportion of pregnant and breastfeeding women expressing hesitation to the COVID-19 vaccine worldwide. Forty-six studies were included, selected from scientific articles available in three scientific databases between 1 January 2020 and 6 February 2022. The vaccine hesitation rate among pregnant and breastfeeding women was 48.4% (95%CI=43.4–53.4%). In a sub analysis by study period, it was 40.0% (95%CI=31.6–46.6%) considering surveys administered in 2020, 58.0% (95%CI=48.9–66.9%) considering surveys administered in the first semester of 2021, and 38.1% (95%CI=25.9–51.2%) considering surveys administered in the second semester of 2021. The main reasons for vaccine hesitation were lack of information about vaccination, opinion that the vaccine is unsafe, and fear of adverse events. Expert opinion: Available evidence in the literature has shown that fighting vaccine resistance is harsh and too slow as a process, considering the rapidity and unpredictability of a pandemic. Health education should be provided in order to improve the willingness of the community, especially for those with lower levels of education.